# Algebra

posted by Anonymous

Write the first five terms of the sequence below.

a_n=4/n!

1. Steve

how about you provide some thoughts on these? This one is especially easy -- just plug in the values of n, from 1 to 5.

## Similar Questions

1. ### Algebra 2

Write an equation for the nth term of the geometric sequence: -12,4,-4/3 I had a_n=-12(3)^(n-1) but that is not a choice on the multiple answers they have = -12(1/3)^(n-1) = 12(-1/3)^(n-1) = -12(-1/3)^(-n+1) = -12 (-1/3)^(n-1)
2. ### math

-Write the arithmetic sequence 21,13,5,-3... in the standard form: a_n= -a_n=a_1+(n-1)d--so a_n=21+(n-1)-8 *a_n=-168-8n why isnt this right?
3. ### Algebra 2

The sequence is defined by a recursion formula. Write the first four terms of the sequence: a_1=9; a_n=3a_n-1
4. ### Algebra 2

The sequence is defined by a recursion formula.Write the first four terms; a_1=-5; a_n=2a_n-1 +7
5. ### Algebra 2

The sequence is defined by a recursion formula, write the first four terms of the sequence; a_1=100; a_n=1/2a_n-1 +4
6. ### Algebra 2

The sequence is defined by a recursion formula. Write the first four terms of the sequence; a_1=0; a_n=5a_n-1 +7
7. ### Math

1.The nth term of a geometric sequence is given by a_n=1/4(4)^n-1 . Write the first five terms of this sequence. 2.The nth term of a a geometric sequence is given by a_n=27(0.1)^n-1 . Write the first five terms of this sequence.
8. ### PreCalculas

The nth term of a a geometric sequence is given by a_n=27(0.1)^n-1 . Write the first five terms of this sequence. Can i get some help
9. ### Algebra II

1. Which represents the first two terms of the sequence: a_1 = 2 and a_n = -2(a_n-1)^2 option a. -8, -128 option b. 16, 1024 option c. -2, 16 option d. 2, -8 2. Which is the seventh term in the sequence: a_n = -1/125 * 5^n-1 option …
10. ### DISCRETE MATH

Determine whether the following is a recursive or explicit. Then, find the first four terms of the following sequence. a) a_n = 〖na〗_(n-1) where a_0 =5 b) a_n = a_(n-1) + 3a_(n-2) where a_0 = 1 and a_1 =2 c) a_n = 2^n …

More Similar Questions